Implementation of Lean Six Sigma for production process optimization in a paper production company - Adefemi Adeodu; Mukondeleli Grace Kanakana-Katumba; Maladzhi Rendani (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: This study aimed at implementing lean six sigma to evaluate the productivity and manufacturing waste in the production line of a paper company Methodology/Approach: The study is a case study in nature. The method illustrates how lean six sigma (LSS) is used to evaluate the existing production process in a paper production company with focus on productivity and manufacturing waste. The study considered a real-time problem of customer's dissatisfaction. The gathered data is based on machine functionality (up time, down time and cycle time); materials and labour flow at every process stages of the production line. The optimization of the production process was based on lean tools like value stream mapping, process cycle efficiency, Kaizen, 5S and pareto chart Findings: Based on lean six sigma application, it was discovered that the present production performance was below standard and more manufacturing wastes were generated. The present productivity and manufacturing wastes are reported as low process cycle efficiency (23.4 %), low takt time (4.11 sec), high lead time (43200sec), high number of products not conforming to six sigma values, high down time (32.64 %) and excess labour flow (33). After the implementation of the lean six sigma tools for certain period of time, there are lots of improvements in the production line in terms of all the parameters considered. Research Limitation/ Implications: The study has demonstrated an application of lean six sigma in the case of solving real-time problems of productivity and manufacturing wastes which have a direct implication on customer's satisfaction. The lesson learned and implications presented can still be further modeled using some lean based software for validity Originality/Value: The study has contributed to the body of knowledge in the field of LSS with focus to process based manufacturing, unlike most literature in the field concentrate more on discrete based manufacturing.
Keywords: 650; Lean manufacturing; lead time; process cycle efficiency; takt time; value added time